Optimizing the train timetable with consideration of different kinds of headway time. Issue 2 (June 2017) - Liu, Pei; Han, Baoming
The train timetable is a crucial document for organization of railway traffic. A high-quality train timetable is not only implementable in operational environment, but also efficient in terms of capacity utilization of railway infrastructure. In this paper, we try to solve the train timetabling problem of a double track high-speed railway line with heavy traffic and trains with different operational speeds are operated. In order to obtain a feasible timetable with high efficiency, different kinds of headway time are distinguished in the process of train timetabling. With a time expanded graph describing train movements, an integer linear programming is formulated. A branch and price algorithm is proposed to solve the model. The case study shows that more trains will be scheduled when different kinds of headway time considered.